Prediction of Long-Term Survival after Coronary Artery Bypass with Bilateral Internal Thoracic Artery Grafting: External Validation of A Contemporary Nomogram - Ioannis K. Toumpoulis; Dimitrios A. Kanistras; Christina K. Pappa; Zoi Zagoriti; Constantine E. Anagnostopoulos; Stavros K. Toumpoulis (Journal of Cardiovascular Development and Disease, 2022)
Background: This study aimed to verify the external validation of a contemporary nomogram in predicting long-term survival after an isolated coronary artery bypass with bilateral internal thoracic artery grafting (CABG-BITA). Methods: Consecutive patients who underwent CABG-BITA at a single center were included in the study. All the predictors of the original risk score (age, diabetes mellitus, chronic obstructive pulmonary disease, congestive heart failure, chronic renal failure, old myocardial infarction, ejection fraction, intra-aortic balloon pump and peripheral arterial disease) were available for analysis. Results: Among the 2846 consecutive patients, a total of 1176 (41.3%) deaths were recorded during the 31,383 patient years of follow-up. The median EuroSCORE II was 2.35, and the median follow-up was 11.1 years. The risk score showed 72.7% overall discriminatory ability as measured by Harrell’s concordance statistic. It showed satisfactory calibration at 10, 15 and 20 years of follow-up. The risk score showed a time-varying nonlinear effect, and accordingly, adjusted long-term survival predictions were calculated. There were subgroups (scores < 50 points) with favorable 20-year survival rates ranging from 77% to 60%. Higher risk subgroups (scores > 90 points) showed poor 20-year survival rates ranging from 22% to 4%. Conclusions: The validated risk score represents a useful algorithm for the detection of patients who could benefit after CABG-BITA with respect to long-term survival. Although further multi-center studies are required worldwide to reveal the usefulness of this score in the clinical setting, its wide adoption may act as a motivation for cardiac surgeons resulting in higher numbers of CABG-BITA procedures.